Low T3 Syndrome as a Predictor of Poor Prognosis in Patients With Pyogenic Liver Abscess - Xu, Jing; Wang, Liang (Frontiers in Endocrinology, 2019)
Aim: There is an association between the low triiodothyronine (T3) state and the poor prognosis for severe acute conditions. However, the correlation between thyroid dysfunction and pyogenic liver abscess (PLA) is unclear. This study aims to figure out how low T3 syndrome is related to the poor prognosis in PLA patients as well as estimate the serum T3 predictive value. Methods: The study consecutively enrolled 240 PLA patients in total with 3-month followed-up period, and defined low T3 syndrome as low T3 level together with non-thyroid disease. Researchers implemented multivariate logistic regression analyses, univariate analysis, as well as receiver-operating characteristic (ROC) curve analysis. Results: Patients with low T3 syndrome had a higher risk of mortality rate (14.3% vs 2.0%), acute hepatic failure (6.8% vs 1.0%) and septic shock (12.1% vs 3.0%) than patients with normal levels of T3 (all P<0.05). Low T3 syndrome served as an independent predictor of death (odds ratio (OR)=5.03, 95% of confidence interval (CI)=1.09-23.05) and all adverse outcomes (odds ratio (OR)=3.63, 95% of confidence interval (CI)=1.84-7.17) following the adjustment of potential confounders in the logistic model. T3 had the largest area under ROC curve (AUC) than T4, FT3, FT4 and TSH in death prediction (AUC=0.901, cutoff value=0.70 nmol/L, P<0.01) and all adverse outcomes (AUC=0.743, cutoff value=0.83 nmol/L, P<0.01). Conclusions: It seems that low T3 syndrome can predict the prognosis of PLA in future clinical practice.